2006
DOI: 10.1353/csd.2006.0042
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Good Practices on Cognitive Development, Learning Orientations, and Graduate Degree Plans During the First Year of College

Abstract: This study estimated separately the unique effects of three dimensions of good practice and the global effects of a composite measure of good practices on the cognitive development, orientations to learning, and educational aspirations of students during their first year of college. Analyses of longitudinal data from a representative sample of colleges and universities were conducted, and net of a battery of confounding influences, measures of good practices were positively related to a number of first-year ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 25 publications
3
113
1
4
Order By: Relevance
“…These process indicators have been empirically linked to student success. Cruce, et al (2006) described the research supporting the predictive validity of each of Chickering and Gamson's (1987) principles. The weight of evidence synthesized by Cruce et al related to each principle is substantial.…”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 99%
“…These process indicators have been empirically linked to student success. Cruce, et al (2006) described the research supporting the predictive validity of each of Chickering and Gamson's (1987) principles. The weight of evidence synthesized by Cruce et al related to each principle is substantial.…”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 99%
“…Research on these good teaching practices demonstrates that many good teaching practices have a positive relationship with many college outcomes (Cruce, Wolniak, Seifert, & Pascarella, 2006;Edison, Doyle, & Pascarella, 1998;Halpin, 1990;Johnson, 1994;Kuh & Hu, 1999;Kuh & Hu, 2001;Kuh & Vesper, 1997;Pascarella, Cruce, Wolniak, & Blaich, 2004;Pascarella, Edison, Serra Hagedorn, Nora, & Terenzini, 1996;Pascarella, Seifert, & Whitt, 2008;Pascarella, Salisbury, & Blaich, 2011;Pascarella & Terenzini, 2005;Umbach & Wawrzynski, 2005). One main college outcomes that is of interest is evaluating the effect of good teaching practices on student learning.…”
Section: Outcomes Of Good Teaching Practicesmentioning
confidence: 99%
“…One such line of research has evaluated the positive influence of interactions with faculty on cognitive skills and intellectual growth (Cruce, Wolniak, Seifert, & Pascarella, 2006;Frost, 1991;Kuh, 1995;Kuh & Hu, 1999;Tsui, 1999). For example, Kuh and Hu (1999) found that student-faculty interaction had significant, positive effects on learning.…”
Section: Outcomes Of Good Teaching Practicesmentioning
confidence: 99%
See 2 more Smart Citations